2019
DOI: 10.20319/pijss.2019.53.99119
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Legislations: Ethical Issues in Domestic Work in Nigeria

Abstract: Recent studies show that domestic work, which cut across age and gender, can have adverse and exploitative consequences for workers, particularly in an unregulated environment. Due to these concerns, international organizations have enacted legislation for a regulated legal environment for domestic work for member nations to domesticate. Nigeria, as a member nation and signatory to the conventions and recommendations, has failed to enact legislation that will regulate the domestic work contractual terms. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…However, the sparse available data show that Nigerian domestic workers are vulnerable to human right abuses in respect of their working conditions. Ogbechie and Oyetunde (2019) in their study found that most domestic workers, particularly live-in domestic workers, are without pay. These workers perform domestic service in exchange for sponsored education, vocational training, free accommodation, meal or extension of economic support to the family member of the domestic workers.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, the sparse available data show that Nigerian domestic workers are vulnerable to human right abuses in respect of their working conditions. Ogbechie and Oyetunde (2019) in their study found that most domestic workers, particularly live-in domestic workers, are without pay. These workers perform domestic service in exchange for sponsored education, vocational training, free accommodation, meal or extension of economic support to the family member of the domestic workers.…”
Section: Introductionmentioning
confidence: 91%
“…However, the requirement that the obligation to pay the national minimum wage applies to only establishments with not less than 25 employees in terms of section 2(a) appears to exclude employers in the domestic work sector. This is because it is rare to find a household that employs up to 25 domestic workers (Ogbechie and Oyetunde 2019). This leaves the remuneration of domestic workers to the discretion of employers.…”
Section: Earningsmentioning
confidence: 99%
See 2 more Smart Citations